Correlation between Students’ Vocabulary and Grammar Mastery to Reading Comprehension in Analytical Exposition Texts - Salsabila, Vanny; Fitrawati, Fitrawati (Universitas Negeri Padang, 2025)
Reading comprehension plays a crucial role in academic success, particularly at the university level, where students are often exposed to complex texts, such as analytical expositions. This study investigates the correlation between students' vocabulary and grammar mastery and their reading comprehension of analytical exposition texts. The population of this study consisted of 7 classes with 176 students in the fourth semester of the English Education program at Universitas Negeri Padang. The sample consisted of 35 students selected through proportional random sampling, where 5 students were chosen from each class using the Wheel of Names website. Three tests had been used to gather the data: a vocabulary mastery test, a grammar mastery test, and a reading comprehension test based on analytical exposition texts. The findings revealed no significant correlation between vocabulary mastery and reading comprehension (r = 0.184, p > 0.05). However, a moderate and significant correlation was determined between grammar mastery and reading comprehension (r = 0.508, p < 0.05). Due to the non-normal distribution of the data, regression analysis could not be performed. These outcomes imply that grammar performs a extra crucial role than vocabulary in students’ capacity to recognize analytical exposition texts. The study recommends that instructors emphasize grammar education in academic reading classes while still keeping vocabulary improvement.